Convergent analysis of genome‐wide genotyping and transcriptomic data suggests association of zinc finger genes with lithium response in bipolar disorder. Issue 7 (14th October 2018) - Pisanu, Claudia; Congiu, Donatella; Costa, Marta; Chillotti, Caterina; Ardau, Raffaella; Severino, Giovanni; Angius, Andrea; Heilbronner, Urs; Hou, Liping; McMahon, Francis J.; Schulze, Thomas G.; Del Zompo, Maria; et al.
Abstract : Lithium is the mainstay treatment in bipolar disorder (BD) for its effectiveness in the acute phases of illness and in prevention of recurrences. Lithium's mechanism of action is complex, and while it modulates the function of hundreds of molecular targets, most of these effects could be unspecific and not relevant for its clinical efficacy. In this study, we applied an integrated analytical approach using genome‐wide expression and genotyping data from BD patients to identify lithium‐responsive genes that may serve as biomarkers of its efficacy. To this purpose, we tested the effect of treatment with lithium chloride 1 mM on the transcriptome of lymphoblasts from 10 lithium responders (LR) and 10 nonresponders (NR) patients and identified genes significantly influenced by the treatment exclusively in LR. These findings were integrated with gene‐based analysis on genome‐wide genotyping data from an extended sample of 205 BD patients characterized for lithium response. The expression of 29 genes was significantly changed by lithium exclusively in LR. Gene‐based analysis showed that two of these genes, zinc finger protein 429 (ZNF429) and zinc finger protein 493 (ZNF493), were also significantly associated with lithium response. Validation with quantitative real‐time polymerase chain reaction confirmed the lithium‐induced downregulation of ZNF493 in LR ( p = .036). Using convergent analyses of genome‐wide expression and genotyping data, we identified ZNF493 as a potential lithium‐responsive target that may be involved in modulating lithium efficacy in BD. To our knowledge, this is the first evidence supporting the involvement of zinc finger proteins in lithium response.